Caffeine as a modulator of redox balance and migration in MDA-MB-231 triple-negative breast cancer cells - Amira, Qanita Hana; Fadilah; Bowolaksono, Anom; Dwiranti, Astari (Institut Teknologi Bandung, 2025)
Caffeine, a widely consumed stimulant, has demonstrated significant effects on cancer cell behavior, particularly in triple-negative breast cancer (TNBC) cells. This study investigates the impact of caffeine on MDA-MB-231 cells, focusing on cell morphology, viability, antioxidant gene expression, and cell migration. Caffeine at concentrations of 10 mM and above induced notable morphological changes, including cell rounding, detachment, and decreased cell density, indicative of cytotoxic effects and cellular stress responses such as apoptosis. Viability assays revealed a dose-dependent reduction in cell survival, with a substantial decline in total cell count at higher caffeine concentrations. The observed decrease in cell viability is associated with the downregulation of antioxidant genes SOD2 and GLO1, suggesting disrupted redox balance and impaired detoxification systems. A significant positive correlation was noted between SOD2 and GLO1 expression levels, indicating their interdependence in antioxidant defense mechanisms. Additionally, caffeine treatment impaired cell migration, as the wound healing assay shows, with higher concentrations significantly hindering wound closure. This effect on migration, relevant for metastasis, aligns with findings from previous studies on caffeine’s influence on cancer cell motility. The results suggest that 10 mM caffeine may serve as an optimal concentration for inducing cellular stress without immediate, widespread cell death, positioning it as a promising candidate for further therapeutic exploration.